Limestone : an alternative material for road base and subbase - Nor Aini, Rosli (Universiti Malaysia Sarawak, UNIMAS, 2004)
This study was carried out to examine the suitability of using limestone as road base and subbase materials. Limestone samples were collected, for laboratory tests, from two selected locations of Sarawak namely Akud Quarry at 21st mile of Kuching-Serian Road and Paku Quarry at Bau.